2016
DOI: 10.1016/j.msec.2016.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Cell growth on 3D microstructured surfaces

Abstract: Chinese Hamster Ovary (CHO) cell cultures were grown on surfaces lithographed with periodic 3D hexagonal microcavity array morphology. The range of microcavity size (inscribed circle diameter) was from 12 μm to 560 μm. CHO cells were grown also on flat surfaces. The characterization was performed with respect to cell growth density (number of nuclei per unit area) by fluorescence optical microscopy and evaluated by correlation function analysis. We found that optimum microcavity radius was 80 μm, concerning to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Furthermore, in the scaffolds with 75 μm wide features, myoblast cells adhered on the peaks of the microstructures and seem to spread beyond the edges of the lines evidencing interconnections, while in the structures 150 μm wide they are totally separated by the valleys and mostly adhered at the peaks of the microstructures. These results may indicate a preferential and thus larger adhesion of myoblast cells in the presence of minor spaces so they can be closer, than microstructures with higher height and wider valleys that hinder or even prevent cells communication …”
Section: Results and Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Furthermore, in the scaffolds with 75 μm wide features, myoblast cells adhered on the peaks of the microstructures and seem to spread beyond the edges of the lines evidencing interconnections, while in the structures 150 μm wide they are totally separated by the valleys and mostly adhered at the peaks of the microstructures. These results may indicate a preferential and thus larger adhesion of myoblast cells in the presence of minor spaces so they can be closer, than microstructures with higher height and wider valleys that hinder or even prevent cells communication …”
Section: Results and Discussionmentioning
confidence: 93%
“…The results demonstrated that the topography dimensions influence substantially cell behavior. SU-8 scaffolds with surfaces composed by hexagons with diameter in the range of the micrometers were fabricated to study the impact of the size in Chinese hamster Ovary (CHO) cell growth . Once again, cell growth density proved to depend directly in the microcavity radius, providing adequate distance for cells communication.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies work with microstructured inorganic or organic surfaces for cells growth. Araujo et al [64] reported on templates consisting of SU-8, an epoxy-based material hexagonal with a periodic pattern of microcavities with a size ranging from 12 to 560 µm and its influence on cell growth of Chinese hamster ovary (CHO) cells. The honeycomb-like structures found the highest cell density of single, separated cells for the 80 µm cavities.…”
Section: Discussionmentioning
confidence: 99%
“…Interactions with the extracellular matrix (ECM), furthermore, influence cell behaviour and have become increasingly important for the understanding of cell development [2, 3]. Alongside the impact of physicochemical matrix composition, various studies have demonstrated that topography alone can significantly modulate cell function [47].…”
Section: Introductionmentioning
confidence: 99%